Upaya Peningkatan Aktivitas Dan Hasil Belajar Fisika Siswa Melalui Penerapan Model Pembelajaran Berfikir Induktif - Mariana, Erni; Kinasih, Ayang (Jurnal Penelitian Pendidikan Fisika, 2021)
The purpose of this study was to determine the increase in activity and student learning outcomes using inductive thinking learning models on the subject and the concept of heat in class X.3 students. The method used is a qualitative type method applied to Classroom Action Research (CAR) which is carried out collaboratively and participatively. The results of this study indicate an increase in activity and student learning outcomes in class X.3 SMA N 1 Sekampung on the concept of heat through the inductive thinking learning model. Student learning activities in the first cycle with an average score of 16 in the good category and in the second and third cycles each increased to 18 in the good category and 19.5 with the good category. Student learning outcomes in the aspect of concept understanding or test questions and LDS increased in the second cycle, the student's absorption capacity was 83% and the learning completeness was 84% and increased in the third cycle, the student's absorption was 85% and the learning completeness was 90%.